Ritodrine-Induced Agranulocytosis: A Case Report and Literature Review. (8th August 2020) - Daimon, Atsushi; Nunode, Misa; Sano, Takumi; Tanaka, Tomohito; Fujita, Daisuke; Ohmichi, Masahide
Abstract : Ritodrine hydrochloride is used for preterm labor, although serious side effects, including agranulocytosis, are reported. We report a case of ritodrine hydrochloride-induced agranulocytosis accompanied by bacteremia due to catheter infection. At 24 weeks of gestation, a female patient presented due to threatened premature labor and was administered continuous intravenous infusion of ritodrine hydrochloride. On day 36 after starting intravenous ritodrine hydrochloride, she was diagnosed with agranulocytosis. The white blood cell and granulocyte count nadirs were 1, 660/ μ l and 438/ μ l. The cumulative dose of ritodrine hydrochloride was 2, 610 mg. Ritodrine therapy was immediately stopped, and she was given an intravenous injection of antibiotics and granulocyte colony-stimulating factor. From her blood culture, methicillin-sensitive Staphylococcus aureus was detected. However, she started vaginal delivery two days after we stopped the ritodrine infusion. When using ritodrine hydrochloride, it is necessary to frequently check the white blood cell count, regardless of the total dose and treatment period.